Influencia del desempleo en el surgimiento de una alteración del estado de ánimo de un adulto del cantón Vinces - Tamayo Ricaurte, Cindy Aracelly (2020)
The adult experiences a series of changes in all aspects of his life but it must be remembered that these changes are normal, complications begin when there are mood alterations that influence and affect his family and personal social life where he cannot perform daily activities such as Before this was carried out for this reason, this case study aimed at an adult who presents alterations in the mood caused by unemployment, proposes the implementation of gradual techniques of cognitive behavioral therapy to improve their symptoms and in turn their lifestyle, to In this case study, the implementation of psychological techniques such as direct observation, semi-structured interview, psychometric tests accompanied by their respective instruments were used, which allowed establishing the respective diagnosis and subsequently carrying out the respective therapeutic plan.